Organisationers hantering av e-WOM på sociala medier : Tre fallstudier: Scandic hotell, Luleå kommun och Lulebo AB - Hadi, Hasanen (2016)
Date: 2016-06-01Level: Master thesis in Business Administration, Specialization Marketing Institution: Department of Business Administration, Technology and Social Sciences – Luleå University of TechnologyAuthor: Hasanen HadiTitle: Organizations Management of e-WOM on Social Media – Three case studies; Scandic hotell, Luleå kommun and Lulebo ABTutor: Anne EngströmKeywords: Social media, WOM, E-WOMPurpose: The purpose of this paper is to increase understanding of the business and organizational management of e-WOM on social mediaMethod: A deductive study in a qualitative manner which is conducted through interviewsConclusion: The discontent or criticism arises and grows in social media is a challenge for organizations. The risk that the businesses damaged by negative e-WOM in the form of complaints and grievances in social media is great because more people can take part of the complaint via negative e-WOM on social media channels. As a result of these challenges in social media, companies should implement some strategies e.g. communicate and engage in social media in order to manage and reduce the risk of e-WOM. If all the complaints and grievances in the form of comments and opinions are handled, the risk of the adverse effects which may occur in the form of negative e-WOM will be minimized. Validerat; 20160629 (global_studentproject_submitter)